Comparison of the diagnostic accuracy of 99 m-Tc-MDP bone scintigraphy and 18 F-FDG PET/CT for the detection of skeletal metastases. (January 2016) - Chang, Connie Y; Gill, Corey M; Joseph Simeone, F; Taneja, Atul K; Huang, Ambrose J; Torriani, Martin; Bredella, Miriam A
Background: Fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) is commonly performed for cancer staging, as it can detect metastatic disease in multiple organ systems. However, there has been some controversy in the scientific literature when comparing FDG PET/CT and technetium-99 m-bone scintigraphy (bone scan) for the detection of skeletal metastases. Purpose: To compare the accuracy of FDG PET/CT with bone scan for the detection of skeletal metastases. Material and Methods: The study group comprised 202 adult cancer patients who underwent both FDG PET/CT and bone scan within 31 days for staging. Bone scans and FDG PET/CT were evaluated by two musculoskeletal radiologists for the presence and location of skeletal metastatic disease. Confirmation of the final diagnosis was based on the CT or magnetic resonance imaging (MRI) appearance, follow-up imaging, or histology. Results: The sensitivity, specificity, and accuracy for detecting skeletal metastatic disease of FDG PET/CT were 97%, 98%, and 98%, respectively, and of bone scan were 83%, 98%, and 93%, respectively. The lesions that bone scan most commonly missed were located in the pelvis, spine, and sacrum. FDG PET/CT missed mostly lesions that were outside of the field of view, but in all of these cases the patient had additional sites of skeletal metastatic disease. Bone scan falsely identified six metastatic lesions and FDG PET/CT falsely identified three metastatic lesions. Conclusion: FDG PET/CT is an accurate technique for detection of skeletal metastases, and is superior to bone scan, especially in the spine and pelvis.